2007
DOI: 10.1002/ijc.22562
|View full text |Cite
|
Sign up to set email alerts
|

Second primary malignancies in females with primary fallopian tube cancer

Abstract: Primary fallopian tube cancer (PFTC) is a rare disease, and its aetiological factors are poorly understood. Studies on PFTC in the setting of 2nd primary malignant neoplasms can provide clues on aetiology and also define the possible side effects of different treatment modalities for PFTC. A cohort of 2,084 cases with first PFTC was extracted from the data from 13 cancer registries from Europe, Canada, Australia and Singapore and followed for second primary cancers within the period 1943-2000. Standardized inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Significant risk increases were seen for colorectal cancer during the second to fifth year after the first PFTC diagnosis, for non‐lymphoid leukemia during the second to tenth year, and for breast cancer during follow‐up 10 years or more after the PFTC. The clustering with cancers of the lung and bladder in PFTC patients may suggest that shared smoking risks may affect the etiology for these cancers, while the excess of colorectal and breast cancers after PFTC may indicate a genetic etiology (54).…”
Section: Incidence Of Pftc and Its Sociodemographic Determinantsmentioning
confidence: 99%
“…Significant risk increases were seen for colorectal cancer during the second to fifth year after the first PFTC diagnosis, for non‐lymphoid leukemia during the second to tenth year, and for breast cancer during follow‐up 10 years or more after the PFTC. The clustering with cancers of the lung and bladder in PFTC patients may suggest that shared smoking risks may affect the etiology for these cancers, while the excess of colorectal and breast cancers after PFTC may indicate a genetic etiology (54).…”
Section: Incidence Of Pftc and Its Sociodemographic Determinantsmentioning
confidence: 99%
“…In hospital-based series, 0.2 -2% of pregnancies are complicated by an adnexal mass, and approximately 1-6 % of these masses are malignant. 4 The aetiology of PFTC is poorly understood; Riska et al 5 suggested smoking as possible risk factor, also the group highlighted a possible genetic aetiology in view of an excess of colorectal and breast cancers after PFTC. PFTC is often presented with non-specific symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the etiological link between the first and subsequent merits attention, but should be considered only one of the multitude of factors which determine the prevalence of MMs and, more particularly, the prevalence of specific combinations of multiple cancers. There are etiological theories concerning the development of subsequent cancers: ( i ) specific treatment effects6, 9; ( ii ) shared risk factors between first and subsequent cancers (lifestyle or environmental factors12, 36); ( iii ) shared genetic predisposition and ( iv ) combinations of the above three 5, 10, 37. Adverse effects of treatment ( i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In 2001, in the USA 8% of the prevalent cancer patients had multiple malignancies (MMs),3 and one of six (16%) newly diagnosed cases in 2004 had MMs 4. The International Agency of Research on Cancer (IARC) has published a series of studies assessing the relative risk of developing second malignancies after a first cancer 5–12. Similar studies have been performed in the Netherlands 13–17.…”
mentioning
confidence: 99%